Osobennosti adaptatsii novorozhdennykh u materey s ozhireniem - L Yu Zernova; T V Kovalenko; N N Popova; N S Strelkov (Ожирение и метаболизм, 2008)
According to various authors, obesity among pregnant recorded at a frequency of 15.5 to 26.9%. There is strong evidence that obesity contributes to complications of pregnancy, childbirth and the postpartum period, provoking the development of gestosis, placental insufficiency, abnormalities of labor, bleeding, et al., Which suggests the possibility of adjustment disorder in the neonatal period in infants of obese mothers. It should be recognized, however, that the available information on the subject are scarce and fragmentary. The purpose of this study was to investigate the features of postnatal adaptation of newborns of mothers with obesity. According to the study found that obesity in women is associated with a high incidence of reproductive disorders, gestational complications and pathological course of labor, resulting in abnormalities in the neonatal adaptation in the postnatal period. Disadaptation syndrome is manifested by the development of jaundice sustained over, edema, transient changes of the cardiovascular system, hypoglycemia. Violations in health are detected in the majority of infants (83.3%) born to mothers with obesity. The most significant pathologies are infections specific to the perinatal period (40.5%), respiratory distress syndrome (3.6%), diabetic fetopathy (4.8%), congenital malformations (2.4%).